MEMBERITAKAN INJIL DI ERA DIGITAL UNTUK MENJAWAB AMANAT AGUNG DALAM DUNIA SERBA DIGITAL - Agnes; Mutiara Mona Sari, Bersyeba Merita Palangga, Veni Valent, Lebrina Maroak (ADISAM PUBLISHER, 2026)
The shift into the digital era has transformed nearly every aspect of human life, including how Christians proclaim the Gospel. This article aims to explore how churches and individual believers can fulfill the Great Commission in a digital world full of challenges. The core issue lies in how the Gospel can be effectively communicated through digital media without compromising its theological depth and spiritual value. This study employs a qualitative descriptive-reflective approach through literature review, examining theological sources, digital research reports, and current ministry practices. The findings reveal that digital platforms represent a new and strategic mission field, yet require adequate theological, ethical, and technical preparedness. Churches must establish a solid foundation of digital theology, empower believers as digital missionaries, and create contextual, transformative content. Additionally, issues such as shallow content, polarization, and instant culture must be addressed wisely to ensure the Gospel remains pure and impactful. In conclusion, digital mission is not merely an option but a faith-driven mandate for today’s ever-changing world.